ABA biosynthesis rather than ABA catabolism is induced by low temperature and inhibits seed germination by activating OsTPP3 - Zhonge Qin; Jiahan Lyu; Zhenning Teng; Shuang Meng; Yan Peng; Dingyang Yuan; Meijuan Duan; Jianhua Zhang; Nenghui Ye (Crop Journal)
Low-temperature (LT) stress is a significant abiotic stress in rice growth, especially under direct seeding cultivation, where low temperatures can significantly affect seed germination and seedling growth of direct-seeded rice, thereby impacting the final yield of rice. In this study, we have identified a trehalose synthesis pathway gene, trehalose-6-phosphate phosphatase 3 (OsTPP3), involved in the regulation of low-temperature (LT) germination in rice, as well as its upstream regulatory factor, the ABA signaling pathway gene OsbZIP23. LT stress induced the accumulation of ABA by upregulating the expression of OsNCED3. Consistently, the overexpression of OsNCED3 significantly inhibited seed germination under LT. RT-qPCR experiments found that the expression of OsbZIP23 was also significantly induced under LT stress and ABA treatment. Overexpression of OsbZIP23 has increased the sensitivity to LT stress of rice seed, resembling the phenotype of OsNCED3 overexpressing seeds. Furthermore, both LT stress and exogenous ABA treatment increased the trehalose content in WT seeds by upregulating the expression of OsTPP3. Enhancing the expression of OsTPP3 or application of exogenous trehalose have significantly increased the sensitivity to LT stress during seed germination. Transcriptional activation and yeast one-hybrid assays demonstrated that OsbZIP23 bound to the promoter of OsTPP3 and activated its expression, which was intensified by LT stress or the application of ABA. Our study discovered an ABA-dependent OsbZIP23–OsTPP3 module that responds to LT stress, inhibiting seed germination under LT conditions by increasing trehalose accumulation, thus might balance the growth and stress resistance and provide a new insight into the genetic improvement of rice cultivars with better LT germination performance.